Pelatihan Penggunaan Perangkat Lunak GeoGebra dalam Pembelajaran Matematika bagi Guru-guru SMA di Wilayah Insana dan Biboki - Elinora Naikteas Bano; Oktovianus R. Sikas; Fried Markus Allung Blegur (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Average National Examination score in 2019 for Mathematics Study Program territory North Central Timor (TTU) was 31.15. This achievment is the lowest average score of the other exams, both at the level TTU district, NTT province, and Nationals. Low learning innovation and teacher creativity often become problems in learning mathematics. Some schools in TTU have average scores below the district average that is Biboki dan Insana selected and trained to utilize software GeoGebra. This training begins with an introduction about GeoGebra and followed by training to solve various mathematical problems using GeoGebra. Then the proses follow-up with distribution of GeoGebra tutorial videos and ongoing mentoring and guidance. After training, 52.38% of partisipants ready to use GeoGebra in their lessons.